2017
DOI: 10.1038/onc.2017.324
|View full text |Cite
|
Sign up to set email alerts
|

ING5 activity in self-renewal of glioblastoma stem cells via calcium and follicle stimulating hormone pathways

Abstract: Stem cell-like brain tumor initiating cells (BTICs) cause recurrence of glioblastomas, with BTIC ‘stemness’ affected by epigenetic mechanisms. The ING family of epigenetic regulators (ING1-5) function by targeting histone acetyltransferase (HAT) or histone deacetylase complexes to the H3K4me3 mark to alter histone acetylation and subsequently, gene expression. Here we find that ectopic expression of ING5, the targeting subunit of HBO1, MOZ and MORF HAT complexes increases expression of the Oct4, Olig2 and Nest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 92 publications
2
19
0
Order By: Relevance
“…S4C-S4F). These results are consistent with previous reports that both NFAT1 and NDEL1 are associated with the activation of Erk (29,30), which plays an important role in the stemness maintenance of GSCs (31,32). In addition, blocking Erk activation using the inhibitor SCH772984 reduced the viability, invasion, self-renewal, and levels of stemness markers in NFAT1-OE G03-GSCs (Supplementary Fig.…”
Section: Nfat1-ndel1 Signaling Affects Erk Activation and Stemness Masupporting
confidence: 93%
“…S4C-S4F). These results are consistent with previous reports that both NFAT1 and NDEL1 are associated with the activation of Erk (29,30), which plays an important role in the stemness maintenance of GSCs (31,32). In addition, blocking Erk activation using the inhibitor SCH772984 reduced the viability, invasion, self-renewal, and levels of stemness markers in NFAT1-OE G03-GSCs (Supplementary Fig.…”
Section: Nfat1-ndel1 Signaling Affects Erk Activation and Stemness Masupporting
confidence: 93%
“…ING5, a member of the ING family of epigenetic regulators that alter histone acetylation and, subsequently, gene expression, increased the expression of stem cell markers and, consequently, brain tumor-initiating cells that cause the recurrence of glioblastomas (stemness) affected by epigenetic mechanisms ( Wang F. et al, 2018 ). Proteomics and cell imaging assays demonstrated that ING5-transfected cells had intracellular Ca 2+ elevation, which was associated with self-renewal, due to an increased expression of several types of Ca 2+ channels, like L-type and P/Q-type voltage-gated Ca 2+ channels, and TRPC ( Wang F. et al, 2018 ). Differentiated glioblastoma cells constitute a distinctive niche compared to glioblastoma stem cells, sending cues to the microenvironment, both as juxtacrine (involving direct contact) or paracrine (through secreted factors).…”
Section: Cancermentioning
confidence: 99%
“…Glioblastoma mutliforme (GBM) is the most common and has the poorest prognosis of any malignant tumor of the central nervous system, which is classified as the fourth stage by WHO. [1][2][3][4] It turns out that the morbidity of GBM among people is as high as 3.19/100,000 through age adjustment by Central Brain Tumor Registry of the United States (CBTRUS). GBM accounts for 45.2% of all primary central nervous system malignant neoplasms and a high 54% of glioma's.…”
Section: Introductionmentioning
confidence: 99%